Lao phrasebook & dictionary - Dobbin, Andrea (Lonely Planet, 2019)
Lonely Planet Lao Phrasebook is your handy passport to the most relevant and useful Lao phrases and vocabulary for all your travel needs. Get recommendations for local dishes and directions to historic sights; all with your trusted travel companion.